Arctan-Based Robust Droop Control Technique for Accurate Power-Sharing in a Micro-Grid - Ineza, M. A.; Saulo, M. J.; Wekesa, C. W. (Engineering, Technology & Applied Science Research, 2022)
Due to the inherent limitations of the Traditional Droop Controller (TDC), an enhanced droop controller, known as Robust Droop Controller (RDC) has been proposed in previous works. However, this controller cannot compensate for the error in measured frequency, which can potentially contribute to the errors in proper reactive power-sharing as well as degrade frequency regulation. This paper introduces an Arctan-Based Robust Droop Controller (ABRDC) that modifies the RDC for L-inverter to address this issue. The controller, rather than utilizing a linear function, utilizes an arctan-based function for power/frequency droop control. Various simulations were performed in Matlab/Simulink to test the performance of the proposed ABRDC. The results showed that it successfully reduces the frequency error, resulting in improved frequency regulation as well as adequate reactive load power-sharing. The comparative study showed that the ABRDC scheme is more effective than the RDC scheme.